Epidemiological Profile and Postpartum Outcome for Severe Preeclamptic Patients - Suher Dafaus; Amel Morgham (Khalij-Libya Journal of Dental and Medical Research, 2021)
Background and objective. Preeclampsia is a multisystemic disorder, which involves the placenta, liver, blood, neurological and cardiovascular systems. It is one of the leading causes of maternal and fetal morbidity and mortality. This study aimed at describing the characteristic features for mothers who had severe preeclampsia and to know the complications during puerperium. Methods. A prospective study conducted over a period from February 2009 up to November 2009 involving 100 pre-eclampsia patients admitted and delivered in Aljalaa Maternity Hospital, Tripoli, Libya. Results. The patients mean age was 33.3 +5.9 years. The mean gestational age at admission time was 36.8+3.2 weeks and 64% of them were term. 58% of the patients with severe preeclampsia had a positive family history of chronic hypertension whereas 42% of patients had a previous history of preeclampsia. 40% of patients were primigravida. The mean systolic blood pressure at admission was 164+15.4 mmHg and the mean diastolic pressure was 113+6 mmHg. The common symptoms were headache, abdominal pain, and blurred vision (54%, 37%, and 31% respectively), whereas 9% of the patients presented with the eclamptic fit. The pregnancy in 66% patients ended by caesarean section, 78% of them were emergency caesarean section. The birth weight of 13% of new-borns was less than 1500 grams. Furthermore, 10% diagnosed with intrauterine fetal death (IUFD) antenatally and 9% died after admission to nursery intensive care unit post-delivery. Conclusion. the effects of hypertensive disorder associated with pregnancy could be prevented by close antenatal care particularly for whose had previous history of preeclampsia. In addition; early recognition and adequate treatment, and timely delivery can prevent preeclampsia and will improve maternal and neonatal outcomes.